Education, training and contexts : studies and essays - Lauglo, Jon [Verfasser]; Se-Yung, Lim [Herausgeber]; Schaack, Klaus [Herausgeber] (Lang, 2003)
"This volume provides an overview over some of the outstanding features of the work of the Norwegian sociologist and comparative educationist Jon Lauglo, who has provided many incisive analyses to the understanding of Norwegian, European, African and international problems and developments in the field of education and training. His publications give evidence of the various social, political and cultural movements and conditions in a large number of industrialized and developing countries and contexts shaping what we usually call in short 'education and training system'; social forces which continue to exert an influence on them - sometimes till present times. One of the outstanding characteristics of Jon Lauglo's work is his combination of comprehensive theoretical approaches (Weber, Bourdieu, Coleman et al.) with meticulous and painstaking empirical research, another one is his rejection of unnecessarily gloomy visions of the educational future in an increasingly globalized world. He has for many years been involved in the development of strategies for poorer nations and in the analysis of educational opportunities of migrant populations in industrialized countries." (Verlag)

Dieses Werk umfasst einige herausragende Artikel des norwegischen Soziologen und vergleichenden Pädagogen Jon Lauglo. Seine Themen: Entwicklungen und Probleme auf dem Gebiet der Erziehungswissenschaft in Norwegen, Europa, Afrika und international; Entwicklung von Bildungsstrategien für Entwicklungsländer; Analyse der Bildungsmöglichkeiten für Migranten in industrialisierten Staaten. Er verbindet umfassende theoretische Analysen mit sorgfältiger empirischer Forschung. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; P 3.2.3 Lehrer; G 2.4 Sozialer Wandel; I 2.2.1 Westeuropa; I 2.3.1 Afrika; Bildungssystem; Lehrer; Soziale Umwelt; Berufsbildung; Bildungscontrolling; Industrieländer; Entwicklungsländer; Internationaler Vergleich; Norwegen; Europa; Afrika